The mercadological challenges faced by the physician entrepreneur (Research, Society and Development, 2022)
Being an entrepreneur is not an easy task, and this becomes more complex when the entrepreneur is also a physician. This occurs because of the busy life and the little free time that these health professionals have. Therefore, this article has as its main theme the marketing setbacks faced by the entrepreneurial physician. Regarding the objective, the aim was to describe the marketing challenges faced on a daily basis by entrepreneurial physicians. Thus, the methodology used was an integrative literature review, with a qualitative approach. The results showed that the challenges are diverse and caused by diversified factors, thus, the physician must seek his differential to stand out in the market. It was also found the lack of a good basis of administration, which are necessary for the good performance of any company, as these subjects are not offered in the medical course, this becomes another challenge to be faced. Examples were also cited of doctors who use social networks as a means of attracting new customers/patients.